Wound dressings. Issue 1 (January 2022) - Holloway, Samantha; Harding, Keith G.
Abstract: The purpose of wound dressings is to support the local wound environment in order to facilitate wound healing. Dressings range from simple or passive dressings that essentially provide a contact layer to protect the wound bed from further damage and maintain a moist environment, to more advanced or interactive dressings that are capable of modifying the physiology of the wound milieu to optimize healing by, for example, promoting debridement, enhancing granulation tissue formation and re-epithelialization, managing exudate levels and bacterial load. There are also bioactive dressings which can change the cellular or biological aspects of the wound, an example of this would be a topical antimicrobial product. Hence a fundamental prerequisite to choosing the most appropriate dressing is having a clear objective in mind. Essential to this is an accurate assessment of the wound. This article will describe the features of the clinical assessment process as a basis for understanding the principles of wound management and provide details of various dressings and devices together with the indications and limitations of their use.